2015
DOI: 10.1159/000439172
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Effect of Complement Factor H Gene Polymorphism in Response to the Initial Intravitreal Injection of Bevacizumab for Wet Age-Related Macular Degeneration

Abstract: Purpose: To compare the functional and morphological response to the initial intravitreal (IVT) injection of bevacizumab in exudative age-related macular degeneration (AMD) patients with the complement factor H (CFH) gene polymorphism T1277C in the Brazilian population. Methods: Twenty-five unrelated patients with treatment-naive exudative AMD underwent an IVT injection of 1.25 mg bevacizumab at the initial presentation (D0) and were reexamined 7 days (D7) and 28 days (D28) later. The time and extent of visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…The alleles in CFH, ARMS2, and VEGFA were associated with genetic anticipation and inadequate response to the anti-VEGF agents in AMD patients [35]. The relationship between the delayed functional and limited response to the injection of bevacizumab and the CFH gene polymorphism T1277C was also identified [36]. In our study, no associations were found between the SNPs of VEGF family genes and the morbidity of AMD.…”
Section: Discussionmentioning
confidence: 49%
“…The alleles in CFH, ARMS2, and VEGFA were associated with genetic anticipation and inadequate response to the anti-VEGF agents in AMD patients [35]. The relationship between the delayed functional and limited response to the injection of bevacizumab and the CFH gene polymorphism T1277C was also identified [36]. In our study, no associations were found between the SNPs of VEGF family genes and the morbidity of AMD.…”
Section: Discussionmentioning
confidence: 49%
“…Smailhodzic et al 36 demonstrated a cumulative effect of high-risk alleles in CFH, ARMS2 , and VEGFA that were associated with a younger age of onset and inadequate response to intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents in individuals with AMD. Medina et al 37 also found that in individuals with a homozygous CC group, variants of the CFH gene polymorphism T1277C were associated with delayed functional and limited morphological response to the initial intravitreal injection of Avastin (bevacizumab) in wet AMD. Therefore, further pharmacogenomic studies may aid in developing a rational guide to treatment regimens and to optimize treatment response tailored to an individual’s genetic background.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In the CFH gene, the CFH Y402H SNP was significantly related to higher doses of bevacizumab in AMD patients (p = 0.02) [25]. The TT genotype for this SNP was associated with a greater improvement in mean visual acuity (p = 0.009) in macular degeneration treated with ranibizumab [25], while the CC genotype was associated with a decreased response if treated with bevacizumab [26]. Furthermore, the CFH Y402H TT genotype was related to a decreased response to PDT in AMD patients (p = 0.04) [27].…”
Section: Introductionmentioning
confidence: 99%